The use of coconut pulp as a feed substrate to methanogenesis inhibitor in in vitro rumen fluid fermentation - Sondakh, E. H. B.; Kalele, J. A. D.; Ratulangi, F. S. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
This experiment was conducted to determine the effect of the adding of coconut pulp in ruminant feed on methane reduction in vitro. Rumen fluid and substrate of forage and concentrate in ratio 60:40 were in this study. This experiment consisted of five treatments of coconut pulp as followed: R1: feed substrates without the coconut pulp; R2: substrate feed with coconut pulp 5%; R3: substrate feed with coconut pulp 10%; R4: Substrate feed with coconut pulp 15% and R5: substrate feed with coconut pulp 20%. Each treatment was conducted to four replications. Fermentation was done using the Hohenheim Gas Test (HGT) incubated at 39oC for 72 hours. At the end of fermentation was determined production of methane, parameters of fermentation, microbial activity, feed digestibility and fatty acids profile of the ruminal fluid. Data obtained were analyzed by using analysis of variance using completely randomized design. The differences of mean values were analyzed by Duncan multiple range test (DMRT). The results showed that methane production has decreased about 13.74%-17.39% when the feed was given coconut dregs 15-20%. Based on the results of the study was concluded that the supplementation of coconut pulp up to 15-20% of 100% dry matter can be used as a substrate of ruminant feed, because it can reduce methane and does not interfere the microbial activity in the fermentation of rumen fluid through in vitro. The supplementation of coconut pulp can be a referencein designing the methanogenic inhibitor feed.